Sheehan's syndrome misdiagnosed as encephalitis: A case report and literature review - Xiao‐Yan Yang; Yong‐Su Zheng; Jin‐Mei Tuo; Hai‐Qing Zhang; Zu‐Cai Xu (Ibrain)
Abstract A 48‐year‐old female patient was hospitalized for 5 days after a cold. Encephalitis was considered after preliminary history and routine examination, but the patient did not show significant improvement after antiviral treatment. At this time, magnetic resonance imaging indicated pituitary atrophy, and the patient's medical history was assessed. She had a history of postpartum bleeding and amenorrhea 15 years ago. The supplementary examination indicated hormonal abnormalities. These suggested that the patient may have had Sheehan's syndrome (SS). After hormone supplementation treatment for 10 days, her condition improved. This case suggested that in female patients with neuropsychiatric disorders with a history of previous postpartum hemorrhage, attention needs to be paid to screening for SS to improve the related diagnosis and treatment rate.